Pengaruh Budaya Organisasi, Motivasi Ekstrinsik, Dan Kepemimpinan Demokratis Terhadap Kepuasan Kerja Karyawan pada PT. Catur Kencana Manajemen Kab. Sleman - Rabit pratama; Prayekti Prayekti; Jajuk Herawati (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2023)
The purpose of this study was to explain the influence of organizational culture, extrinsic motivation, and democratic leadership on employee job satisfaction. As the research population are employees of PT. Chess Kencana District Management. Sleman Prov. In Yogyakarta. sampling technique using census. As for data collection using questionnaires and multiple linear regression data analysis. The results of the study found that organizational culture, extrinsic motivation, and democratic leadership had a significant effect on job satisfaction.